Bleu Pour Toujours (Blue Forever) - Macha Petre (Vernacular: New Connections in Language, Literature, & Culture, 2025)
Since this short story is written in French, the abstract below is available in both English and French. Bleu pour toujours (« Blue Forever ») is a short story blending poetry and science fiction. In the near future, war, pollution, and human activity have devastated our world. The blue sky exists only in history books or old photographs. Amid this gray, monotonous despair, an unnamed, ageless, and genderless character escapes one evening and makes unsettling discoveries. Something is stirring. Upon waking, they find everyone has vanished, and the laws of the universe have been upended. In place of the sky now lies an ocean teeming with whales, a species thought to be extinct. Seeking meaning and soothed by the whales' songs, the character begins to search for what has replaced the ocean, only to find themselves confronted with the vastness of the celestial expanse. Bleu pour toujours est une nouvelle entre la poésie et la science-fiction. Dans un futur proche, la guerre, la pollution et l’activité humaine ont ravagé notre monde. Le ciel bleu n’existe plus que dans les livres d’histoires ou sur les vieilles photos. Au milieu de ce désespoir gris et monotone, un personnage sans nom, sans âge ni genre, s’échappe un soir et fait des découvertes troublantes. Quelque chose se prépare. À son réveil, tout le monde a disparu, et les règles de l’univers ont été bouleversées. À la place du ciel se trouve désormais l’océan peuplé de baleines, espèce pourtant disparue. En quête de sens, bercé par le chant des géants flottant au-dessus de sa tête, le personnage se met alors à chercher ce qui se trouve désormais à la place de l’océan, avant de se retrouver face à l’immensité céleste.
Keywords: N/A